The Meaning of the Term Al-Fasad in the Qur’an: A Semantic Perspective of Toshihiko Izutsu - Adila, Khonsa; Rha'in, Ainur; Bisyri, Mohammad Hasan (Aqwal: Journal of Qur'an and Hadis Studies, 2025)
Background and Objectives: This study investigates the semantic dimensions of the term al-fasād in the Qur’an using Toshihiko Izutsu’s semantic approach. The objective is to provide a comprehensive understanding of the concept’s implications for individuals and society, particularly as a Qur’anic warning against destructive human behavior. Methodology: The research employs a qualitative descriptive method grounded in Izutsu’s systematic semantic analysis. It identifies the basic and relational meanings of al-fasād and traces their development from the pre-Islamic (Jahiliyyah) context to the classical Islamic period.  Main Findings: The findings show that al-fasād encompasses not only physical destruction but also moral and social corruption that can destabilize societal structures. Within the Qur’anic discourse, the term often appears alongside related concepts such as ẓulm (injustice) and al-kharāb (ruin), forming a broad semantic network. The analysis further reveals that al-fasād functions both as an individual transgression and as a collective social phenomenon capable of leading to systemic disorder. Contributions: By applying Izutsu’s semantic framework, the study contributes to identifying and clarifying the conceptual structure of al-fasād in the Qur’an. It demonstrates how semantic-conceptual analysis enriches the understanding of Qur’anic terminology and supports the development of more context-sensitive interpretation. Conclusions: The research highlights the importance of semantic analysis in contemporary Qur’anic studies and emphasizes the urgency of preserving social, moral, and environmental order within Muslim society as part of addressing al-fasād in its various forms.